PERAN PENGURUS CABANG IPNU DALAM MENUMBUHKAN MINAT BERORGANISASI BERLANDASKAN NILAI-NILAI ASWAJA AN-NAHDLIYAH DI MADRASAH TSANAWIYAH HASYIM ASYARI KOTA BATU - Aldy Candra Andriyansa; Ach. Faisol; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
In this study, researcher focus on the role of PC IPNU city Batu to develop organizational interest based on the value “Aswaja An-Nahdliyah” in Mts Hasyim Asary. Reseaecher use qualitative methods. Data collection prosedure is using interviews, observations, and documentation. The result of this study is to develop organizational interest based on the value